2018
DOI: 10.1038/s41598-017-18663-6
|View full text |Cite
|
Sign up to set email alerts
|

Universal type/subtype-specific antibodies for quantitative analyses of neuraminidase in trivalent influenza vaccines

Abstract: Both influenza viral hemagglutinin and neuraminidase can induce protective immune responses in humans. Although the viral hemagglutinin antigens have been quantified in influenza vaccines, the amounts of neuraminidase remain undetermined. Using comprehensive bioinformatics analyses of all neuraminidase sequences, we identified highly conserved and subtype-specific peptide epitopes within each of N1, N2 and type B neuraminidase groups. Mono-specific antibodies generated against these peptides bound to their res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The authors found that 14 to 35% of influenza A virus-specific MAbs induced by natural infection bound NA, whereas only 0 to 2% did so after vaccination. They confirmed that the NA antigen is poorly represented in many subunit vaccines and that the quality and quantity of NA in different vaccines varies (30,31).…”
mentioning
confidence: 78%
“…The authors found that 14 to 35% of influenza A virus-specific MAbs induced by natural infection bound NA, whereas only 0 to 2% did so after vaccination. They confirmed that the NA antigen is poorly represented in many subunit vaccines and that the quality and quantity of NA in different vaccines varies (30,31).…”
mentioning
confidence: 78%
“…The NA from H3N2 viruses has been reported to be more stable than N1 and thus the relatively constant signal observed for N2 NA could be due to the protein’s better stability. 7 In any case, this analysis appears to support the notion that NA content in commercial vaccines is highly variable, 30 although such a conclusion cannot be drawn without quantification using a calibration standard. Future studies using VXI-sNA to assess fresh lots of vaccine are needed to address the magnitude of lot-to-lot and year-to-year NA content variation.…”
Section: Discussionmentioning
confidence: 53%
“…28 Two alternative methods utilizing immunochemistry have been described recently. 29,30 However, one of these methods was designed solely for the quantification of NA from H1N1 strains 29 and another, while resistant to antigenic change due to the probing of a conserved, linear epitope, is not sensitive to changes in protein stability due to the requirement of degrading the NA protein before quantification. 30…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [ 32 ] identified highly conserved and subtype-specific peptide epitopes within each of N1, N2 and type B neuraminidase proteins using Geneious 7.0.6 software program. These peptides were shown to generate mono-specific antibodies against their respective subtype/type in experimental rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Immune response to peptides is influenced by the way they are presented to the immune system, and therefore a multifunctional delivery systems coupling the antigen with adjuvant is needed [ 34 ]. This approach has been addressed subsequently by many researchers and has shown similar effects [ 32 ]. Gold nanoparticles mediated OVA peptide delivery [ 35 ], peptides adsorbed on poly (D, L-lactide-co-glycolide) (PLGA) particles as a controlled-release vaccine delivery system [ 36 ].…”
Section: Discussionmentioning
confidence: 99%